Legacies of War - Films Media Group (2000)
From munitions stockpiles to psychological trauma, the effects of war linger long after conflict formally ends. This award-winning documentary examines several postwar situations around the world, highlighting ongoing efforts to repair physical, social, and personal damage. Powerful footage captures the dangers of unexploded bombs in Germany and land mines in Mozambique; the reconstruction of Guatemalan society after 36 years of civil war; the plight of refugees in Kosovo; and the difficult task many African villages face of accepting children back into the community who have fought as soldiers. Several experts also comment, including Mary Robinson, UN High Commissioner for Human Rights. A United Nations Production. (32 minutes).
fma32766
Mode of access: World Wide Web.
System requirements: Windows Media, etc.